Educational Technology in Crisis - Fainholc, Beatriz (2008)
The presentation of the historical epistemological path is needed to understand and reconsider the discipline of Educational Technology in articulation to contributions of rupturistic theorists in order to reach to a critical proposal and a revision of its field. This field is facing a deep crisis within a time of world crisis, specially in the southern hemisphere and in contexts of migration of nomad or poor users. The technology should be 'appropriate', socially grounded and culturally adequate in its pedagogical mediations depending on diverse scenarios and actors, who will select and combine traditional elements with virtual ones to be delivered in an electronic formats. Appropriate and Critical Technology is a special technological discipline and a knowledge field where we cultivate open and reflexive special knowledge, towards research and contrast at socio-educational practices, mediated by pedagogical projects and materials articulated with ICT. Its study objects are the educational-technological mediations as historical -cultural- semiologic and didactic environments and tools in diverse formats, which provoke different domains of the socio-cognitive structuring of learners in a situated and distributed way, inscribed within formal and non- formal, face-to-face and distance teaching practices.